1993
DOI: 10.2466/pms.1993.77.3f.1291
|View full text |Cite
|
Sign up to set email alerts
|

Self-Perceived Creativity and Vividness of Mental Imagery

Abstract: We report the joint influence of creativity factors on mental imagery among 1361 university students of Fine Arts, Mathematics, and Geography and History. Creativity accounted for 1% of the variance in imagery among Fine Arts students, 4% among Mathematics students, 2% among Geography and History students, and 3% in the whole sample.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1999
1999
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…Justi cation for this is based upon the proper methodological treatment of subjective measures in experimental psychology (Valentine, 1992). Several papers were rejected on these grounds (Campos & Gonza lez, 1993;Campos & Pe rez, 1994;Durndell & Wetherick, 1977;Kuzendorf, 1982). (3) Inadequate reporting.…”
Section: Literature Searches and Inclusion Criteriamentioning
confidence: 99%
“…Justi cation for this is based upon the proper methodological treatment of subjective measures in experimental psychology (Valentine, 1992). Several papers were rejected on these grounds (Campos & Gonza lez, 1993;Campos & Pe rez, 1994;Durndell & Wetherick, 1977;Kuzendorf, 1982). (3) Inadequate reporting.…”
Section: Literature Searches and Inclusion Criteriamentioning
confidence: 99%
“…With time, many empirical studies appeared that demonstrated a weak relationship between imagination and divergent thinking (Parrott and Strongman, 1985 ; Campos and Perez, 1989 ; Campos and González, 1993 ), which is confirmed by the meta-analysis summing up these studies (LeBoutillier and Marks, 2003 ). It therefore became justified to treat these constructs as distinct and relatively independent components of creativity, each having its own measurement specificity.…”
Section: Introductionmentioning
confidence: 89%
“…Studies investigating correlations between creativity and vividness of imagery have been performed on college students (Campos & Gonzdlez, 1993a, 1993bForisha, 1978;Khatena, 1975;Lindauer, 1977;Schmeidler, 1965), high school students (Gonzdlez, Campos & P6rez, 1997;Fontao, 1996;Campos & P6rez, 1989), and gifted elementary students (Shaw & DeMers, 1986). A few studies have specifically investigated persons involved in or studying for a profession in the fine arts (Campos & Gonzdlez, 1993a, 1993bDavies & Talbot, 1987) or persons identified as aesthetic (Lindauer, 1977). Researchers studying creativity have used a variety of tests to measure creativity and imagery; Table 1 lists the studies and tests used to investigate the correlation between creativity and vividness of imagery.…”
Section: Previous Studies Of Creativity and Imagerymentioning
confidence: 99%